Effect of retrograde condensation and stress sensitivity on properties of condensate gas reservoirs - Li, Nan; Li, Haosen; Tan, Xianhong; Zhang, Lijun; Liu, Yuwei (Frontiers in Energy Research, 2023)
In order to study the phenomenon of gas well productivity decline caused by retrograde condensation damage in the production of low-permeability condensate gas reservoirs, a stress sensitivity experiment was carried out on three cores using constant confining pressure and variable inner pressure. Nitrogen and condensate gas were used as the experimental fluid for each core, and the percentages of core skeleton damage and retrograde condensation damage were analyzed. Based on the experimental results, the gas well production was calculated considering stress sensitivity and retrograde condensation. When the net stress is less than 7 MPa, retrograde condensation damage is the main cause of permeability decline. When the net stress is between 7 and 20 MPa, the effects of core skeleton damage exceed the retrograde condensation damage. After the net stress reaches 20 MPa, the core skeleton damage accounts for more than 90% of the total damage. The above results indicate that the core skeleton damage is the main cause of reservoir permeability decline in gas well production. Furthermore, gas well production decreases by 97.65% when retrograde condensation is considered.